Asymmetric α‐Amination of Aldehydes by a Recyclable Resin‐Supported Peptide Catalyst. Issue 2 (16th January 2013) - Tanaka, Tatsuyoshi; Akagawa, Kengo; Mitsuda, Masaru; Kudo, Kazuaki
Abstract The asymmetric α‐amination of aldehydes was performed using a resin‐supported peptide catalyst. A tri‐ or tetrapeptide with an N‐terminal D‐Pro‐Aib sequence efficiently catalyzed the reaction in a highly enantioselective manner. The supported catalyst could be easily recovered by filtration and reused at least ten times.